THE CLARITY OF REFERENDUMS: AN INSTRUMENT FOR MANAGING THE (DIS)CONTINUITY AND PERCEPTION OF CHANGE - Miloš, Matija (Pravni zapisi, 2022)
Seen as a precondition for a referendum, clarity requires a clear referendum question and a clear majority for or against an outcome. In this article I argue clarity is not only an enabler of individual referendums but one way to politicize their context. In separating what is clear from what is obscure, clarity imposes the twin requirements of homogeneity and predictability. These, in turn, presuppose an interpretation of acceptable political (dis)continuities beyond the referendum as well as of perception of change. This reading of clarity shows how the referendum does not only manage change to which it is explicitly addressed, but that the purported voice of “the people” may at the same time be an instrument of clarity that imagines and normatively orders the referendum’s surroundings.